The Role of Microvascular Obstruction and Intra-Myocardial Hemorrhage in Reperfusion Cardiac Injury. Analysis of Clinical Data - Ryabov, Vyacheslav V. (2024)
Microvascular obstruction (MVO) of coronary arteries promotes an increase in mortality and major adverse cardiac events in patients with acute myocardial infarction (AMI) and percutaneous coronary intervention (PCI). Intramyocardial hemorrhage (IMH) is observed in 41–50% of patients with ST-segment elevation myocardial infarction and PCI. The occurrence of IMH is accompanied by inflammation. There is evidence that microthrombi are not involved in the development of MVO. The appearance of MVO is associated with infarct size, the duration of ischemia of the heart, and myocardial edema. However, there is no conclusive evidence that myocardial edema plays an important role in the development of MVO. There is evidence that platelets, inflammation, Ca+2 overload, neuropeptide Y, and endothelin-1 could be involved in the pathogenesis of MVO. The role of endothelial cell damage in MVO formation remains unclear in patients with AMI and PCI. It is unclear whether nitric oxide production is reduced in patients with MVO. Only indirect evidence on the involvement of inflammation in the development of MVO has been obtained. The role of reactive oxygen species (ROS) in the pathogenesis of MVO is not studied. The role of necroptosis and pyroptosis in the pathogenesis of MVO in patients with AMI and PCI is also not studied. The significance of the balance of thromboxane A2, vasopressin, angiotensin II, and prostacyclin in the formation of MVO is currently unknown. Conclusive evidence regarding the role of coronary artery spasm in the development of MV hasn’t been established. Correlation analysis of the neuropeptide Y, endothelin-1 levels and the MVO size in patients with AMI and PCI has not previously been performed. It is unclear whether epinephrine aggravates reperfusion necrosis of cardiomyocytes. Dual antiplatelet therapy improves the efficacy of PCI in prevention of MVO. It is unknown whether epinephrine or L-type Ca+2 channel blockers result in the long-term improvement of coronary blood flow in patients with MVO.